Evaluation of the Canal Transportation by OneShape and Neolix Rotary Systems in the Mesial Root of Mandibular First Molars by Cone Beam Computed Tomography - Amir Maghsoudlourad; Marjan Kazeminia; Maryam Rasooli (پزشکی بالینی ابن سینا, 2023)
Background and Objective: One of the most important stages of root canal treatment is the correct and complete preparation of the root canal. This study aimed to compare the amount of canal transportation in two nickel titanium files, OneShape and Neolix. Materials and Methods: In this experimental study, 30 extracted mandibular first molar teeth with 25-35-degree curvature were selected for periodontal reasons and randomly divided into two groups (n=15 each). A cone beam computed tomography (CBCT) scan was obtained from the teeth before the intervention. Followingly, the teeth of each group were prepared by the desired file (OneShape and Neolix) according to the manufacturer's instructions. Another CBCT scan was obtained from the teeth at the same angle. The amount of transportation was analyzed from the mesiodistal aspect at two distances of 3 and 9 mm from the apex. The preparation time of each tooth was also recorded by a chronometer. Data were analyzed by independent t-tests (α=0.05). Results: The mean transport at a distance of 3 mm from the apex in the OneShape and Neolix groups was 0.19 and 0.1 mm, respectively. The mean transport at a distance of 9 mm from the apex was 0.2 and 0.1 mm in the OneShape and Neolix groups, respectively. Statistically, there was no significant difference in the amount of transportation between the two groups at the distance of 3 mm (P=0.055) and 9 mm (P=0.39). The mean preparation time was longer in the OneShape group than in the Neolix one; however, it did not show a statistically significant difference (P=0.73). Conclusion: Both Neolix and OneShape files can maintain the curvature of the canal and are suitable for curved canals in terms of shaping ability.